ANALISIS KONTRIBUSI EKSPOR KOPI TERHADAP PDB SEKTOR PERKEBUNAN DI INDONESIA - suwali, suwali; Hendri Putranto, Afif; Bintang Panunggul, Victor; Putriana Nuramanah Kinding, Dwi; Noviani, Faizah (Perwira Journal of Economics & Business, 2022)
The success of a country in developing its economy is characterized by the value and growth rate of gross domestic product (GDP). Exports can encourage a country's GDP growth. Plantation is one of the agricultural sub-sectors that has an important influence on Indonesia's development into the developing country it is today. The large number of coffee plantations makes Indonesia one of the largest coffee producing countries in the world after Brazil, Vietnam and Colombia. There are several local coffees that are known throughout the world, including Gayo coffee, Toraja coffee, Lampung coffee and Aceh coffee. Increasing Indonesian exports is always pursued with various strategies, including export expansion strategies, especially non-oil and gas products to encourage economic growth. This research aims: (1) to find out how coffee exports have developed in Indonesia for the period 2011 to 2020. (2) to know the contribution of coffee exports to GDP in the plantation sector in Indonesia for the period 2011 to 2020. This research uses a case study method with a quantitative approach. The data used is secondary data for the period 2011 to 2020, namely coffee production volume for the 2011-2020 period, GDP in the plantation sector for the 2011-2020 period, volume and value of Indonesian coffee exports for the 2011-2020 period, volume and value of cocoa, palm oil and rubber exports for the period. 2011-2020. The analysis used is descriptive statistical analysis and analysis of the contribution of coffee exports to GDP in the plantation sector. The research results explain that: (1) The development of Indonesian coffee exports is fluctuating with a downward trend. The average Indonesian coffee export was 693,136 tons per year during the period 2011 to 2020. (2) Coffee exports made a positive contribution to increasing GDP in the plantation sector in Indonesia, compared to exports of other plantation commodities such as palm oil, cocoa and rubber. The average contribution of coffee exports to GDP in the plantation sector in Indonesia was 3.13 percent per year during the 2011 to 2020 period.